2015
DOI: 10.1111/lam.12423
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal potential ofAvicennia schauerianaStapf & Leech. (Acanthaceae) againstCladosporiumandColletotrichumspecies

Abstract: This study shows that Avicennia schaueriana extracts have a high potential for the growth inhibition of Colletotrichum and Cladosporium ssp. and will provide a starting point for discovering new natural products with antifungal activity. Their development is of particular interest to organic production systems where synthetic fungicides cannot be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…In particular, mangroves produce a wide variety of structurally novel natural agents with biochemical profiles [13]. Avicennia marina is a mangrove species of the Acanthaceae family, and discoveries of its chemical compounds have received much attention [14]. A. marina has been used as a traditional medicine for the treatment of skin diseases, rheumatism, ulcers, and smallpox.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mangroves produce a wide variety of structurally novel natural agents with biochemical profiles [13]. Avicennia marina is a mangrove species of the Acanthaceae family, and discoveries of its chemical compounds have received much attention [14]. A. marina has been used as a traditional medicine for the treatment of skin diseases, rheumatism, ulcers, and smallpox.…”
Section: Introductionmentioning
confidence: 99%
“…The various fruit and root solvent extracts of A. officinalis also showed strong antimicrobial activity against various pathogenic bacteria as listed in Table 6 against E. coli, E. aerogenes, K. pneumoniae, P. aeruginosa, B. subtilis, L. delbrueckii, S. aureus and S. pyogenes, B. cereus and E. Faecalis, E. cloacae, P. vulgaris and so on (Sharief & Umamaheswararao 2011;Sharief et al 2014bSharief et al , 2015. Fardin and Young (2015) evaluated a high growth inhibition of A. schaueriana leaf extracts against plant fungal Colletotrichum and Cladosporium sp.. Using thin layer chromatography bioautography, petroleum ether and chloroform fractions of ethanolic stem extract of this plant showed antifungal activity against C. sphaerospermum, C. cladosporioides and C. lagenarium with many active bands in the range of Rf = 0·72 to Rf = 0·55.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…MIC value of leaf extract on spore germination of C. musae and A. alternata was observed at 10 mg ml -1 and 30 mg ml -1 respectively. In composition, Fardin and Young (2015) have reported that MIC of ethanolic extract of Avicennia schaueriana leaves on growth of C. gloeopsporioides is more than 5 mg ml -1 by agar dilution assay.…”
Section: Antifungal Activity Of C Aromaticus Leaf Extract By Agar Wementioning
confidence: 99%
“…Small amounts (5 μl) of the mixture was spotted on a 20 cm x 10 cm precoated thin layer chromatographic (silica gel 60-F-254) plates (0.5 mm thickness, Merck, Germany). They were developed in the solvent system dichloro methane: methanol (99 : 1 v/v), for about 1 hour (Fardin and Young, 2015). Developed chromatogram was observed under ultra violet (UV) light and subsequently under visible light after spraying p-anisaldehyde reagent and heating to 105 0 C. The retention factor (Rf) values of all the spots were determined.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 1 more Smart Citation